Dry matter accumulation of winter wheat (Triticum aestivum L.) at different distances from tree line under Poplar (Populus deltoides) boundary plantation - Sirohi, Chhavi; Bangarwa, K.S.; Dhillon, R.S.; Handa, A.K.; Chavan, S.B.; Arunachalam, A. (Indian Journal of Agroforestry, 2021)
Boundary plantation (BP) agroforestry system (AFS) is one of the most acceptable and preferable agroforestry systems due to its advantage of minimum interference with intercrops and provision of range of environmental services (ES). To further optimize the efficiency of AFS, there is a need to identify suitable tree-crop combinations and limiting competition for resources. It is necessary to screen acceptable intercrop varieties for their performance in certain geometry. In that context, the present research article focused on performance of five winter wheat varieties (WH-1105, WH-542, HD-2967, HD-943 and DPW-621-50) based on two consecutive years with a row of 7- and 8-year old deciduous poplar trees in East-West and North-South directions at different distances from tree-base. Considerable reduction in dry matter accumulation was found near tree line at a distance of 0-2 and 2-4 m, for all the wheat varieties during all the growth stages as compared to sole crop (devoid of BP). Among wheat varieties, the minimum reduction (%) in dry matter accumulation was found in HD-2967 in both row directions (E-W and N-S) during two consecutive years of the study. The results showed that the cultivation of wheat variety HD-2967 with poplar boundary planation will be more beneficial for farmers as compared to other wheat varieties towards the end of the rotation of poplar.